1998
DOI: 10.1111/j.1432-2277.1998.tb01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeat orthotopic liver transplantation in the 1990s: is it justified?

Abstract: Repeat orthotopic liver transplantation (ReOLT) is controversial because of limited donor organ availability and increasing health care costs. The purpose of this study is to analyse and compare the outcome of reOLT in the 1990s and the 1980s. Prospective data of 1077 adult OLT from the Liver Unit database were used for the study. The log-rank test was used for statistical analysis. Between January 1982 and December 1996, a total of 1077 adult OLTs were performed including 107 reOLTs. The proportion of retrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Retransplantation of the liver (reOLT) after failure of the first graft is considered to carry a higher risk, with higher morbidity and lower survival than for the first transplantation [l, 2,3,4,5,6,7,8,9,10,111. In consideration of the often lower survival rate after reOLT, the increasing donor shortages, the pressure of increasing numbers of retransplant candidates on the waiting lists, and the higher costs of such procedures, it is important for one to evaluate the results of reOLT in order to compare the outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retransplantation of the liver (reOLT) after failure of the first graft is considered to carry a higher risk, with higher morbidity and lower survival than for the first transplantation [l, 2,3,4,5,6,7,8,9,10,111. In consideration of the often lower survival rate after reOLT, the increasing donor shortages, the pressure of increasing numbers of retransplant candidates on the waiting lists, and the higher costs of such procedures, it is important for one to evaluate the results of reOLT in order to compare the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of the often lower survival rate after reOLT, the increasing donor shortages, the pressure of increasing numbers of retransplant candidates on the waiting lists, and the higher costs of such procedures, it is important for one to evaluate the results of reOLT in order to compare the outcome. From the literature, different predictive factors for survival after reOLT are known [4,5,6,7,12,13,14,15,16,17, 181, but they were not always acquired by multivariate analysis [4,6,7,12,13,141. The present study evaluates the results of reOLT in adult patients at our institution, with special emphasis on outcome and independent predictive factors for survival.…”
Section: Introductionmentioning
confidence: 99%
“…1 Approximately 15% of patients who receive a transplant will require liver retransplantation (re-LT) for a variety of reasons, including primary graft nonfunction (PGNF), chronic rejection, and disease recurrence. 2,3 It has been shown that the outcome of re-LT is worse than that of primary liver transplantation (PLT; first transplantation). 3,4 However, it is unclear whether the poor outcome is a reflection of the underlying cause of allograft failure requiring re-LT or caused by other confounding variables.…”
mentioning
confidence: 99%
“…2,3 It has been shown that the outcome of re-LT is worse than that of primary liver transplantation (PLT; first transplantation). 3,4 However, it is unclear whether the poor outcome is a reflection of the underlying cause of allograft failure requiring re-LT or caused by other confounding variables. Many factors, including age, race, cause of liver disease, United Network for Organ Sharing (UNOS) status, creatinine level, diabetes, obesity, hypertension, and heart disease, influence posttransplantation survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation